Depression and anxiety in a community sample with epilepsy in Brazil - S Stefanello; L Marín-Léon; P T Fernandes; L M Li; N J Botega (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To estimate the frequency of depression/anxiety and to establish the social, epilepsy and psychiatric characteristics in individuals with epilepsy. METHOD: A cross-sectional study was employed to evaluate 153 subjects with epilepsy who were identified in a previous community-based survey. First, a structured interview was conducted, followed by a psychiatric evaluation. Subjects with depression were compared to those without, and subjects with anxiety were compared to those without. RESULTS: The prevalence of anxiety and depression was 39.4 and 24.4%, respectively. Both were associated with low schooling (OR 3.8, 95% CI 1.6 to 9.0 and OR 2.8, 95% CI 1.2 to 6.5 for depression and anxiety, respectively), lifetime suicidal thoughts (OR 4.4, 95% CI 1.9 to 10.3 and OR 3.6, 95% CI 1.7 to 7.7) and lifetime suicide attempts (OR 9.3, 95% CI 2.6 to 32.8 and OR 6.9, 95% CI 1.8 to 26.4). CONCLUSION: The high rates of depression and anxiety reinforced the need for recognition and treatment of mental disorders in epilepsy.